Medullary Thyroid Carcinoma - perspective after the 2015 ATA guidelines - Martins, Ana Margarida (2017)
Medullary thyroid carcinoma (MTC) is a rare neuroendocrine tumor (1-2% of thyroid cancers) derived from the thyroid C cells producing calcitonin. Most MTC (75%) are sporadic, however, there are hereditary forms (25%) that are part of the multiple endocrine neoplasia syndrome type 2, type 2A and 2B. All the patients with these syndromes have a germline mutation of the RET proto-oncogene and about 50% of the patients with sporadic form have somatic mutations of the same gene. Early diagnosis and treatment are essential. The gold standard for CMT diagnosis of a suspicious thyroid nodule is the fine needle aspiration biopsy (FNAB), along with the measurement of serum calcitonin. Genetic testing, with screening for mutations of the RET gene, should be performed to all patients. The only curative treatment of CMT is total thyroidectomy with resection of the required cervical ganglion compartments. In patients with residual, recurrent or metastatic disease, the most appropriate treatment is still less clear, because most patients have indolent courses with slow progression for several years. Thereby, in most cases the prognosis is relatively good, and distant metastases are the main cause of death. Recently, two tyrosine kinase inhibitors, vandetanib and cabozantinib, have been approved for the treatment of progressive and symptomatic CMT and there are already several other inhibitors in clinical trials. These agents are static inhibitors of the disease, having no lytic or destructive action. For this reason, further studies are needed to understand the molecular basis of MTC and consequently find new systemic therapies that permanently treat metastatic disease. This review outlines advances in the etiopathogenesis, clinical presentation, diagnosis, staging, genetic testing and fundamentally the treatment of CMT, in light of the most recent evidence.